2013
DOI: 10.1155/2013/972370
|View full text |Cite
|
Sign up to set email alerts
|

Dissection of Mechanisms of a Chinese Medicinal Formula: Danhong Injection Therapy for Myocardial Ischemia/Reperfusion InjuryIn VivoandIn Vitro

Abstract: Traditional Chinese medicine uses a systemic treatment approach, targeting multiple etiological factors simultaneously. Danhong injection (DHI), a very popular Chinese medicine injection, is reported to be effective for many cardiovascular conditions. The primary active ingredients of DHI, and their systemic and interrelated mechanism have not been evaluated in an established myocardial ischemia/reperfusion (MI/R) model. We identified the main active constituents in DHI, including hydroxysafflor yellow A (A), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
38
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 33 publications
0
38
0
Order By: Relevance
“…Formulated based on TCM theory of “activating and promoting blood circulations to dissipate blood stasis and dredge collaterals”, DHI, a China food and drug administration approved injectable drug has been widely used in clinics with proven efficacy and safety [29] for treatment and prophylaxis of various cardio-cerebrovascular diseases, such as ischemic-reperfusion injury, atherosclerosis, and acute coronary syndrome [20, 25, 30]. Previously, we found that DHI reversed vascular remodeling and exerted an antihypertensive effect through the Kallikrein-kinin system up-regulation in SHR [27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Formulated based on TCM theory of “activating and promoting blood circulations to dissipate blood stasis and dredge collaterals”, DHI, a China food and drug administration approved injectable drug has been widely used in clinics with proven efficacy and safety [29] for treatment and prophylaxis of various cardio-cerebrovascular diseases, such as ischemic-reperfusion injury, atherosclerosis, and acute coronary syndrome [20, 25, 30]. Previously, we found that DHI reversed vascular remodeling and exerted an antihypertensive effect through the Kallikrein-kinin system up-regulation in SHR [27].…”
Section: Discussionmentioning
confidence: 99%
“…DHI is composed of extracts from Radix Salviae miltiorrhizae (Danshen) and Flos Carthami tinctorius (Honghua) [19] and has been used with proven efficacy and safety for treating various cardio-cerebrovascular diseases [20]. Although, DHI has many components, the main pharmacologically active components include phenolic acids, diterpenes, and flavonoids (salvianolic acid, danshensu, tanshinone, safor yellow etc.)…”
Section: Introductionmentioning
confidence: 99%
“…HSYA, one of the major active compounds of C. tinctorius L., has also been investigated for its ability to treat ischemic diseases including myocardial ischemia [33] and cerebral ischemia [25,34,35]. However, the protective effects of HSYA in these cases could not be explained solely by its antioxidant property.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that DHI exhibited diverse pharmacological effects, including protection against vascular endothelium injury [2,3] , improvements in atherosclerosis and microcirculation [4] , and neuroprotective effects [5] . It has also been suggested that DHI might have a dose-dependent protective effect on promoting angiogenesis and mesenteric microcirculation in acute hypoxia [6,7] . In addition, an experimental study indicated that DHI had a concentration-response relationship in promoting angiogenesis potentially via the increased expression of vascular endothelial growth factor (VEGF) [8] .…”
Section: Introductionmentioning
confidence: 99%